Role of the Mycobacterium marinum ESX-1 Secretion System in Sliding Motility and Biofilm Formation - Lai, Li-Yin; Lin, Tzu-Lung; Chen, Yi-Yin; Hsieh, Pei-Fang; Wang, Jin-Town (Frontiers in Microbiology, 2018)
Mycobacterium marinum is a close relative of Mycobacterium tuberculosis that can cause systemic tuberculosis-like infections in ectotherms and skin infections in humans. Sliding motility correlates with biofilm formation and virulence in most bacteria. In this study, we used a sliding motility assay to screen 2304 transposon mutants of M. marinum NTUH-M6885 and identified five transposon mutants with decreased sliding motility. Transposons that interrupted the type VII secretion system (T7SS) ESX-1-related genes, espE (mmar_5439), espF (mmar_5440), and eccA1 (mmar_5443), were present in 3 mutants. We performed reverse-transcription polymerase chain reaction to verify genes from mmar_5438 to mmar_5450, which were found to belong to a single transcriptional unit. Deletion mutants of espE, espF, espG (mmar_5441), and espH (mmar_5442) displayed significant attenuation regarding sliding motility and biofilm formation. M. marinum NTUH-M6885 possesses a functional ESX-1 secretion system. However, deletion of espG or espH resulted in slightly decreased secretion of EsxB (which is also known as CFP-10). Thus, the M. marinum ESX-1 secretion system mediates sliding motility and is crucial for biofilm formation. These data provide new insight into M. marinum biofilm formation.